Transmission Line based Envelope Amplifier for Envelope Tracking in PA Systems - Eriksson, Jonatan; Persson, Fredrik (My University, 2013)
The aim of this thesis was to investigate the possibility of using a transmission line (TL) based converter as an envelope amplifier (EA) for envelope tracking in a radio frequency power amplifier (RF PA) system. A TL based EA can supply fast voltage modulation but requires impedance match between the characteristic impedance of the TL, and the PA’s supply terminal impedance (STI). Hence, a first step in this thesis was to investigate the characteristics of the PA’s STI. A second step was to construct a prototype of an EA, using a lumped transmission line as energy accumulator. The EA was then tested together with the PA in order to draw further conclusions whether a TL based EA is suitable for ET of PA systems. The result from the PA characterization provided two descriptions of the STI. However, the EA prototype was designed after the STI description that seemed to enable a beneficial ET operation. Despite the PA characterization it was, and still is, a bit unclear what features of the STI a pulsed supply voltage would excite during an EA to PA integration. However, the result from the integration indicated a non beneficial STI behavior. The conclusion from this report is that the studied inverse class F GaN PA does not seem to be suitable for ET with a TL based EA.
Keywords: Elektroteknik och elektronik; Elkraftteknik; Electrical Engineering, Electronic Engineering, Information Engineering; Electric power engineering